Campanhas publicitárias de escolas de língua inglesa : entre discursos e subjetivações - Kiminami, Aline Yuri (2016)
The aim of this study was to analyze, in the current discourses circulating about the English Language (EL), who is the contemporary subject configured and subjectified in the representations provided by Brazilian EL school's advertising campaigns. In order for this study to occur, the need/obligation of learning the EL which is imposed to the subjects was questioned, in search of how the representation(s) of EL students take place in the most well-known EL schools in the market, as well as how these representations produce subject positions. The contributions of the Brazilian National Curriculum Parameters (PCNs) were used as aid in this analysis, for we see them as a deployment that produces discourses about the EL in an institutional context. The analysis built on from a theoretical-methodological background based on the French discursive analysis, especially in the works of Michel Foucault, with contributing theories by Pierre Bourdieu and authors form the language teaching and cultural studies fields. The advertisements were taken as an enunciative series and gathered in four enunciative frameworks, with basis on the following regularities: Work, Success, Challenge and Mobility. After carrying out the analysis, the insertion of the EL in the school's national curriculum was perceived as a contemporary form of governmentality and biopower, since the government manages the population through that curricular imposition, as to prepare the citizens for a work market which demands the EL knowledge as a prerequisite for the attainment of higher ranked and more varied job positions. In the advertisements which revolve around the term "work", a dichotomy was established between those who do and those who not know the EL, leading to what is central in the "success" framework: those who have mastered the EL possess the cultural capital required for them to be able to celebrate conquests. In the framework in which the EL is dealt with as a "challenge", a regularity was noticed between the aspects mentioned by the PCNs and the adverts, in the sense that the EL is viewed as a tool (paraskeué) which will serve as a shield so that the subject may occupy the subject position of interlocutor in a market that may prove itself to be aggressive. Therefore, the EL is a form of 'care of the self'. In the last enunciative framework, 'EL as a Language of Mobility', the EL also establishes a strong relation between what the PCNs state as to the importance of culture in the teaching of the EL, and the advertising campaigns which subjectify the subjects as 'world citizens', with the power of cultural and geographical mobility through the mastering of this specific knowledge, the EL. In an overarching analysis of the enunciative series, we conclude that the EL is represented as a cultural capital and a form of care of the self. The subject represented in the advertisements is mostly young and when the contrary is present, a specific production of meaning is established from the use of the mature subject's image. The same happens with the use of the male figure (predominant in the 'EL as a language of challenge') or the female one (EL as a Language of Mobility). The discourse related to the EL functions in the enunciative series as a desire object, which emerges as a possible founding fault of the subject. The subject may or may not, as it is exposed to the representations built by the adverts, identify in itself the urge/need to learn the EL due to the constitutive fault the campaigns subjectifications may cause.